Repeatability and Reproducibility of Pseudocontinuous Arterial Spin-Labeling–Measured Brain Perfusion in Healthy Volunteers and Patients with Glioblastoma - Zhou, Limin; Udayakumar, Durga; Wang, Yiming; Pinho, Marco C.; Wagner, Benjamin C.; Youssef, Michael; Maldjian, Joseph A.; Madhuranthakam, Ananth J. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Arterial spin-labeling (ASL) MRI has gained recognition as a quantitative perfusion imaging method for managing patients with brain tumors. Limited studies have so far investigated the reproducibility of ASL-derived perfusion in these patients. This study aimed to evaluate intrasession repeatability and intersession reproducibility of perfusion measurements using 3D pseudocontinuous ASL (pCASL) with TSE Cartesian acquisition with spiral profile reordering (TSE-CASPR) in healthy volunteers (HV) and patients with glioblastoma (GBM) at 3T and to compare them against 3D pCASL with gradient and spin echo (GRASE).MATERIALS AND METHODS: This prospective study (NCT03922984) was approved by the institutional review board, and written informed consent was obtained from all subjects. HV underwent repeat pCASL evaluations 2–4 weeks apart between November 2021 and October 2022. Patients with GBM were recruited for longitudinal MRI from September 2019 to February 2023. Intrasession repeatability (HV and GBM) and intersession reproducibility (HV only) of pCASL were assessed using linear regression, Bland–Altman analyses, the intraclass correlation coefficient (ICC) with 95% CI, and within-subject coefficients of variation (wsCV).RESULTS: Twenty HV (9 men; mean age, 25.1 [SD, 1.7] years; range, 23–30 years) and 21 patients with GBM (15 men; mean age, 59.8 [SD, 14.3] years; range, 28–81 years) were enrolled. In imaging sessions, 3D pCASL-measured perfusion with TSE-CASPR and GRASE, respectively, achieved high R2 values (0.88–0.95; 0.93–0.96), minimal biases (-0.46-0.81; -0.08-0.35 mL/100 g/min), high ICCs [95% CI], 0.96–0.98 [0.94–0.98]; 0.96–0.98 [0.92–0.99]), and low wsCV (6.64%-9.07%; 5.20%-8.16%) in HV (n = 20) and patients with GBM (n = 21). Across imaging sessions, 3D pCASL in HV (n = 20) achieved high R2 values (0.71; 0.82), minimal biases (-1.2; -0.90 mL/100 g/min), high ICC [95% CI] values (0.85 [0.81–0.89]; 0.90 [0.87–0.93]), and low wsCV values (13.82%; 9.98%).CONCLUSIONS: Our study demonstrated excellent intrasession repeatability of 3D pCASL-measured cerebral perfusion in HV and patients with GBM and good-to-excellent intersession reproducibility in HV. 3D pCASL with GRASE performed slightly better than 3D pCASL with TSE-CASPR in HV; however, in patients with GBM, 3D pCASL with TSE-CASPR showed better performance in tumor regions with a nearly 2-fold higher SNR. ASL-measured perfusion could serve as a noncontrast quantitative imaging biomarker to facilitate the management of patients with GBM.ASLarterial spin-labelingCASPRCartesian acquisition with spiral profile reorderingGBMglioblastomaGRASEgradient and spin echoHVhealthy volunteersICCintraclass correlation coefficientM0proton-density-weighted imageNSAnumber of signals averagedpCASLpseudocontinuous arterial spin-labelingPLDpostlabel delayQIquantitative imagingwsCVwithin-subject coefficients of variation